2010
DOI: 10.1051/0004-6361/201014848
|View full text |Cite
|
Sign up to set email alerts
|

No detection of large-scale magnetic fields at the surfaces of Am and HgMn stars

Abstract: Aims. We investigate the magnetic dichotomy between Ap/Bp and other A-type stars by carrying out a deep spectropolarimetric study of Am and HgMn stars. Methods. Using the NARVAL spectropolarimeter at the Télescope Bernard Lyot (Observatoire du Pic du Midi, France), we obtained high-resolution circular polarisation spectroscopy of 12 Am stars and 3 HgMn stars. Results. Using least squares deconvolution (LSD), no magnetic field is detected in any of the 15 observed stars. Uncertaintiies as low as 0.3 G (respecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 38 publications
3
60
0
Order By: Relevance
“…Numerous investigations of magnetism in such stars (e.g. Borra & Landstreet 1980;Glagolevskij et al 1985;Shorlin et al 2002;Aurière et al 2010;Makaganiuk et al 2011) have found no convincing evidence for fields in this class of stars with uncertainties often in the range of a few G up to a few tens of G. Furthermore, α And has been specifically investigated with the MuSiCoS (13 observations, typical σ ∼ 30-60 G) and ESPaDOnS (5 observations, typical σ ∼ 6-19 G) spectropolarimeters without any significant detection of a nonzero longitudinal field or of any Stokes V signature indicative of a non-zero field ).…”
Section: Repeated Observations Of Non-magnetic Starsmentioning
confidence: 99%
“…Numerous investigations of magnetism in such stars (e.g. Borra & Landstreet 1980;Glagolevskij et al 1985;Shorlin et al 2002;Aurière et al 2010;Makaganiuk et al 2011) have found no convincing evidence for fields in this class of stars with uncertainties often in the range of a few G up to a few tens of G. Furthermore, α And has been specifically investigated with the MuSiCoS (13 observations, typical σ ∼ 30-60 G) and ESPaDOnS (5 observations, typical σ ∼ 6-19 G) spectropolarimeters without any significant detection of a nonzero longitudinal field or of any Stokes V signature indicative of a non-zero field ).…”
Section: Repeated Observations Of Non-magnetic Starsmentioning
confidence: 99%
“…At the same time, all systematic studies of the magnetic field in HgMn stars reported its absence (Shorlin et al 2002;Wade et al 2006;Folsom et al 2010;Aurière et al 2010;Makaganiuk et al 2011b). In the best cases, an upper limit set on the strength of the mean longitudinal magnetic field is a few Gauss (Aurière et al 2010;Makaganiuk et al 2011b).…”
Section: Introductionmentioning
confidence: 95%
“…For instance, Wade et al (2006) searched for a magnetic field in α And. They analyzed magnetic field measurements obtained with three different polarimeters and concluded that the star has no longitudinal magnetic field stronger than about 6−19 G. Folsom et al (2010) performed a similar analysis for AR Aur, once again finding no field stronger than 20−40 G. Finally, Auriere et al (2010) presented an analysis of a small sample of three bright, sharp-lined HgMn stars, reporting no magnetic field detections at the level of 1−3 G.…”
Section: Introductionmentioning
confidence: 98%
“…First, with the exception of the four stars studied by Wade et al (2006) and Auriere et al (2010), previous work was not particularly precise, possibly missing weak magnetic fields which are still capable of causing chemical spot formation. Second, they included a small number of HgMn stars, often with a strong emphasis on the most slowly rotating ones.…”
Section: Introductionmentioning
confidence: 99%